Effects of Sentiment on Impulsive Buying Behavior: Evidence of COVID-19 in Indonesia - Ali Mursid (Journal of Economics, Business, and Accountancy Ventura, 2020)
Abstract This study aims to investigate the effects of positive and negative sentiment on impulsive buying behavior among Indonesia people based on the theory of stimulus organism response (S-O-R). First, it examines how COVID-19 information, information credibility, and scarcity affect positive sentiment and negative sentiment. Second, it verifies the influence of positive sentiment and negative sentiment on impulsive buying tendencies and impulsive buying behavior. Third, this study verifies impulsive buying tendency impacts impulsive buying behavior. Data was collected from Indonesian people living in a COVID-19 red zone with an online survey via Google form. In total, 320 respondents completed the survey and data analysis employs confirmatory factor analysis (CFA) and structural equation modelling (SEM).  The result found that COVID-19 information and information credibility have a positive effect on positive sentiment, while it has an insignificant effect on negative sentiment. Scarcity has a positive effect on negative sentiment; on the other hand, it has no significant effect on positive sentiment. Both positive sentiment and negative sentiment have positive effects on impulsive buying tendencies.  Only positive sentiment has a positive effect on impulsive buying behavior, while negative sentiment does not. Finally, impulsive buying tendencies have a positive effect on impulsive buying behavior.   AbstrakPenelitian ini bertujuan untuk menginvestigasi pengaruh positif sentimen dan negative sentimen terhadap perilaku pembelian tidak terencana masyarakat Indonesia berpijak pada teori stimulus organism response (S-O-R). Pertama, penelitian ini menguji bagaimana pengaruh informasi tentang COVID-19, kredibilitas informasi, dan kelangkaan terhadap sentimen positif dan sentimen negatif. Kedua, memverifikasi pengaruh sentimen positif dan sentimen negatif terhadap kecenderungan untuk melakukan pembelian tidak terencana dan perilaku pembelian tidak terencana. Ketiga, memverifikasi pengaruh kecenderungan untuk melakukan pembelian tidak terencana dan perilaku pembelian tidak terencana. Pengumpulan data penelitian ini dilakukan terhadap orang-orang Indonesia yang tingga di zona merah COVID-19 melalui survey online dengan Google form. Secara total ada 320 responden berpartisipasi dalam survey ini, kemudian data dianalisis menggunakan analisis confirmatory (CFA) dan struktural equation modeling (SEM). Hasilnya menunjuukan bahwa informasi tentang COVID-19 dan kredibilitas informasi mempunyai pengaruh positif terhadap sentimen positif, tetapi tidak mempunyai pengaruh yang signifikan terhadap sentimen negatif. Kelangkaan mempunyai pengaruh positif terhadap sentimen negatif, sebaliknya tidak mempunyai pengaruh yang signifikan terhadap sentimen positif. Baik sentimen positif maupun sentimen negatif mempunyai pengaruh positif terhadap kecenderungan untuk melakukan pembelian tidak terencana. Hanya, sentimen positif yang mempunyai pengaruh positif terhadap perilaku pembelian tidak terencana, sedangkan sentimen negatif tidak berpengaruh. Terakhir, kecenderungan untuk melakukan pembelian tanpa rencana mempunya pengaruh positif terhadap perilaku pembelian tidak terencana.